2022
DOI: 10.1101/2022.06.14.22276393
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nirmatrelvir plus ritonavir for early COVID-19 and hospitalization in a large US health system

Abstract: Background: In the EPIC-HR trial, nirmatrelvir plus ritonavir led to an 88% reduction in hospitalization or death among unvaccinated outpatients with early COVID-19. Clinical impact of nirmatrelvir plus ritonavir among vaccinated populations is uncertain. Objective: To assess whether nirmatrelvir plus ritonavir reduces risk of hospitalization among outpatients with early COVID-19 in the setting of prevalent SARS-CoV-2 immunity and immune evasive SARS-CoV-2 lineages. Design: Population-based cohort study anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 16 publications
3
54
0
Order By: Relevance
“…This reflects evidence that individual risk-level, vaccination status, and time of treatment initiation will likely influence treatment effectiveness [24]. It also acknowledges real-world studies suggesting reduced effectiveness with the newer Omicron variant [4,[7][8][9][10] and potentially reduced effectiveness in low-risk individuals [10]. In addition, there is evidence of people re-testing positive after their course of nirmatrelvir/ritonavir was completed, accompanied by a resurgence of symptoms, something that had not been seen in trials [14].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This reflects evidence that individual risk-level, vaccination status, and time of treatment initiation will likely influence treatment effectiveness [24]. It also acknowledges real-world studies suggesting reduced effectiveness with the newer Omicron variant [4,[7][8][9][10] and potentially reduced effectiveness in low-risk individuals [10]. In addition, there is evidence of people re-testing positive after their course of nirmatrelvir/ritonavir was completed, accompanied by a resurgence of symptoms, something that had not been seen in trials [14].…”
Section: Discussionmentioning
confidence: 95%
“…On the basis of its current price and observed efficacy, the FDA has given emergency use authorization to nirmatrelvir/ritonavir for treatment of the elderly and other high-risk adults, regardless of vaccination status [6]. Some observers have questioned the breadth of this decision, noting that other studies have failed to replicate the effectiveness observed in the initial trial [7][8][9][10] and that nirmatrelvir/ritonavir's efficacy remains unproven in vaccinated patients [11,12], in addition to the risks posed by serious drug interaction and toxicity [13] and the uncertainty of rebound infections and symptoms [14,15]. Still others have wondered whether the substantial reduction in risks of hospitalization and death in patients receiving nirmatrelvir/ritonavir might justify expanding the indications for treatment far beyond the highest-risk patient population [16].…”
Section: Introductionmentioning
confidence: 99%
“…Excluding these patients would not be reflective of real-world use and could introduce a selection bias, as shown in a US real-world study in which excluding COVID-19 diagnoses coinciding with admissions led to lower hospitalization rates versus the overall population. 29 Our approach is reinforced by monthly hospitalization rate data reported by the US CDC of 7.0%, 5.9%, 8.5%, 8.5%, 4.6%, and 3.7% (excluding patients with missing or unknown hospitalization status) for December 2021−May 2022, 30 which are broadly similar to those within our study (6.1%, 6.3%, 10.1%, 7.8%, 4.8% and 3.2%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Available real-world nirmatrelvir/ritonavir effectiveness studies conducted in the US (Massachusetts and New Hampshire) and Israel during the Omicron period identified 0.4%−0.7% hospitalization rates within 14−35 days among older (ie, ≥40-year-old or ≥50-year-old) patients who received nirmatrelvir/ritonavir compared with 1.0%−1.9% among those who did not. 29, 31 An additional descriptive study found that <1% of US patients who received nirmatrelvir/ritonavir were hospitalized or visited the emergency department in the 5−15 days following treatment. 32 By contrast, a Hong Kong study identified 4.4% and 6.2% hospitalization rates among nirmatrelvir/ritonavir and non-nirmatrelvir/ritonavir recipients, respectively, within 28 days of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Three more real-world analyses evaluating the use of nirmatrelvir–ritonavir during the omicron wave are also available. 7 , 8 , 9 One study from the USA that included patients aged 50 years and older, 7 one from Israel that analysed a subgroup of patients aged 65 years and older, 8 and another from Israel that included patients with a mean age of 68·5 years, 9 showed that early nirmatrelvir–ritonavir therapy was associated with reductions in the risks of hospitalisation or death, or both, in these groups of patients with COVID-19.…”
mentioning
confidence: 99%